A Meeting of the Minds: Informal Agreements and Social Norms - Krupka, Erin L.; Leider, Stephen; Jiang, Ming (Management Science, 2017)
Using coordination games, we elicit social norms directly for two different games where either an agreement to take the first best action has been reached or where no such agreement exists. We combine the norms data with separately measured choice data to predict changes in behavior. We demonstrate that including social norms as a utility component significantly improves predictive performance. Then we compare social norms to guilt aversion and lying aversion. We estimate that honoring an agreement in the double dictator game is worth giving up approximately 10% of total earnings and more than 120% in the Bertrand game. We show that informal agreements affect behavior through their direct effect on social norms as well as through an indirect effect on beliefs. This paper was accepted by Uri Gneezy, behavioral economics.